Co-coated ternary positive electrode material and preparation method and application thereof

By setting a metal oxide-phosphate co-coating shell on the surface of the nickel-cobalt-manganese core and performing a co-precipitation reaction in a micro-channel reactor, the problems of structural damage and poor compatibility of the nickel-cobalt-manganese ternary cathode material under high voltage are solved. problem, achieving efficient preparation of materials and improving electrochemical performance.

CN119361673APending Publication Date: 2025-01-24JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411495809.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Nickel-cobalt-manganese ternary cathode material is prone to irreversible phase change under high voltage charging conditions, resulting in structural damage and reduced cycle life, and poor compatibility with electrolyte, which easily forms an unstable solid electrolyte interface layer, affecting battery performance.

Method used

Set the metal oxide-phosphate-phosphates of the nickel-cobalt-manganese core to cover the shell, and a co-sedimentation reaction is performed in the microcordless reactor to improve the consistency of the reaction rate and the product.

Benefits of technology

The structural stability and thermal stability of the ternary cathode material are significantly improved, side reactions are reduced, electrochemical performance is improved, and energy consumption and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101230200000151
    Figure BDA0005101230200000151
Patent Text Reader

Abstract

The invention provides a co-coated ternary positive electrode material as well as a preparation method and application thereof. The co-coated ternary positive electrode material comprises a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell, by taking the total mass of the ternary positive electrode material as a calculation reference, the mass ratio of the metal oxide-phosphate co-coated shell is 5-20wt%. The metal oxide-phosphate co-coated shell is arranged on the surface of the nickel-cobalt-manganese inner core, so that the structural stability and the thermal stability of the nickel-cobalt-manganese ternary positive electrode material are improved, the compatibility of the nickel-cobalt-manganese ternary positive electrode material with an electrolyte is improved, side reactions are reduced, and the electrochemical performance of the material is improved; high-speed mixing of the materials is realized, the reaction temperature is conveniently and accurately controlled, the reaction rate is obviously improved, the energy consumption and the cost are reduced, and large-scale popularization and application are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and relates to a ternary positive electrode material, and in particular to a co-coated ternary positive electrode material and a preparation method and application thereof. Background Art

[0002] Nickel-cobalt-manganese ternary cathode material is one of the commonly used cathode materials in lithium-ion batteries. By combining nickel, cobalt and manganese, it can release energy at different voltage platforms, thereby providing a higher energy density. Among them, the addition of nickel significantly increases the capacity of the material, allowing it to store more energy in the battery; the addition of manganese helps to improve the thermal stability of the material and reduce the risk of thermal runaway, thereby improving the safety of the battery; compared with other high-capacity cathode materials such as lithium cobalt oxide, nickel-cobalt-manganese ternary cathode materials reduce the expensive cobalt content, thereby reducing material costs while maintaining a higher energy density.

[0003] However, under high-voltage charging conditions, the lattice of the nickel-cobalt-manganese ternary positive electrode material may undergo an irreversible phase change, resulting in the destruction of the material structure, affecting the cycle life and performance of the battery. In addition, under high voltage, the positive electrode material is prone to side reactions with the electrolyte to form an unstable solid electrolyte interface (SEI) layer, thereby consuming the electrolyte and increasing the internal resistance of the battery, reducing battery performance. During the battery's charge and discharge process, especially under high temperature conditions, transition metals such as nickel and cobalt are easily dissolved from the positive electrode material into the electrolyte, resulting in battery capacity decay and performance degradation.

[0004] In this regard, technicians generally use coating technology to modify the surface of the positive electrode material, but the uniformity and integrity of the coating layer are difficult to ensure, which in turn affects the overall performance of the material. The coating process may introduce new defects, such as cracks or holes, which can easily become the source of battery performance degradation.

[0005] In addition, the traditional coprecipitation reaction used to prepare nickel-cobalt-manganese ternary positive electrode materials generally has the problems of long production cycle, relatively high energy consumption and low reaction efficiency. It often takes several days to react and consumes a lot of manpower and material resources. With the increasing shortage of resources and the increasingly prominent environmental problems brought about by economic development, fine chemical companies are facing the requirements of energy conservation and emission reduction, green development and the gradual realization of automated production. Therefore, choosing a scientific and reasonable chemical reaction route and exploring new green and applicable technologies are one of the main ways to achieve the above requirements. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a co-coated ternary positive electrode material and a preparation method and application thereof. By arranging a metal oxide-phosphate co-coated shell on the surface of the nickel-cobalt-manganese core, the structural stability and thermal stability of the nickel-cobalt-manganese ternary positive electrode material are improved, its compatibility with the electrolyte is improved, side reactions are reduced, and the electrochemical properties of the material are improved. At the same time, a microchannel reactor is used in the preparation process to achieve high-speed mixing of materials, facilitate precise control of the reaction temperature, significantly improve the reaction rate, reduce energy consumption and cost, and facilitate large-scale promotion and application.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a co-coated ternary positive electrode material, wherein the co-coated ternary positive electrode material comprises a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell.

[0009] Taking the total mass of the ternary positive electrode material as the calculation basis, the mass proportion of the metal oxide-phosphate co-coated shell is 5-20wt%, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0010] The present invention arranges a metal oxide-phosphate co-coating shell on the surface of the nickel-cobalt-manganese core. This inert material has high thermal stability. Using it as a co-coating shell significantly improves the performance of the ternary positive electrode material in a high temperature environment and reduces the risk of thermal runaway. The co-coating shell enhances the structural stability of the ternary positive electrode material and reduces the volume expansion and contraction during the charge and discharge process, thereby extending the cycle life of the battery.

[0011] In addition, the co-coated shell acts as a physical barrier, reducing the direct contact between the electrolyte and the ternary positive electrode material, thereby reducing the decomposition rate of the electrolyte and extending the service life of the battery. At the same time, it inhibits the dissolution of transition metals in the ternary positive electrode material during the charge and discharge process, reduces the concentration of metal ions in the electrolyte, thereby slowing down the attenuation of the battery capacity and improving the electrochemical performance of the material.

[0012] Preferably, the chemical formula of the nickel-cobalt-manganese core is: Li a Ni x Co y Mn z O 2; Wherein, 1≤a≤1.5, for example, a=1, 1.1, 1.2, 1.3, 1.4 or 1.5, 0.6≤x≤0.8, for example, x=0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78 or 0.8, 0.08≤y≤0.18, for example, y=0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17 or 0.18, and x+y+z≤1, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Preferably, in the metal oxide-phosphate co-coated shell, the metal oxide includes any one of aluminum oxide, zinc oxide or tin oxide, or a combination of at least two of them. Typical but non-limiting combinations include a combination of aluminum oxide and zinc oxide, a combination of zinc oxide and tin oxide, a combination of aluminum oxide and tin oxide, or a combination of aluminum oxide, zinc oxide and tin oxide, and aluminum oxide is further preferred.

[0014] Preferably, in the metal oxide-phosphate co-coated shell, the phosphate includes any one of lanthanum phosphate, aluminum phosphate or cerium phosphate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of lanthanum phosphate and aluminum phosphate, a combination of aluminum phosphate and cerium phosphate, a combination of lanthanum phosphate and cerium phosphate, or a combination of lanthanum phosphate, aluminum phosphate and cerium phosphate, and lanthanum phosphate is further preferred.

[0015] Preferably, in the metal oxide-phosphate co-coated shell, the mass ratio of metal oxide to phosphate is (0.2-2):1, for example, it can be 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1 or 2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In the present invention, the mass ratio of metal oxide to phosphate affects the uniformity and integrity of the co-coated shell. Limiting the mass ratio to within the range of (0.2-2):1 helps to form a continuous and uniform co-coated shell, thereby effectively isolating the positive electrode material from direct contact with the electrolyte. At the same time, due to the different electrical conductivity of metal oxide and phosphate, a reasonable limitation of the mass ratio of the two helps to further optimize the ionic and electronic conductivity of the co-coated shell, thereby significantly improving the charge and discharge performance of the positive electrode material.

[0017] In a second aspect, the present invention provides a method for preparing the co-coated ternary cathode material as described in the first aspect, the preparation method comprising the following steps:

[0018] (1) mixing nickel salt, cobalt salt, manganese salt and deionized water to obtain a ternary salt solution;

[0019] (2) preparing a base liquid in a microchannel reactor, then introducing a ternary salt solution, a precipitant solution and a complexing agent solution, and simultaneously starting material circulation, introducing a protective gas into the microchannel reactor, so that the materials are fully mixed in the reactor for a coprecipitation reaction, and obtaining a nickel-cobalt-manganese ternary precursor after solid-liquid separation;

[0020] (3) mixing a nickel-cobalt-manganese ternary precursor and a lithium salt for solid phase sintering to obtain a nickel-cobalt-manganese core material;

[0021] (4) Mixing the nickel-cobalt-manganese core material, metal oxide and phosphate, and subjecting them to ball milling and heat treatment in sequence to obtain the co-coated ternary positive electrode material.

[0022] The present invention carries out a co-precipitation reaction in a microchannel reactor, and its internal microchannel design can achieve rapid and efficient material mixing, thereby ensuring uniform distribution of reactants in the reactor, significantly improving the reaction rate and product consistency, and reducing energy consumption and costs. At the same time, the microchannel reactor can provide precise temperature control, which is crucial for the preparation process of temperature-sensitive ternary precursors. There is no dead zone in the reaction space, the materials react fully, and the obtained ternary precursor has a very high specific surface area, which further improves the electrochemical properties of the positive electrode material.

[0023] In the present invention, the microchannel reactor is a conventionally used reactor in the art, and any reactor can be used as long as the corresponding functions can be achieved. Therefore, the specific structure of the microchannel reactor is not particularly limited herein.

[0024] In addition, since the materials are in a circulating flow state in the microchannel reactor, the base liquid prepared in advance will be fully mixed with the ternary salt solution, the precipitant solution and the complexing agent solution during the circulation process.

[0025] Furthermore, the present invention can effectively avoid the blockage of the product obtained by the coprecipitation reaction in the pipeline by reasonably controlling the introduction flow rate of the protective gas and the tube diameter of the microchannel reactor. As long as the smooth outflow of the product can be guaranteed, the introduction flow rate of the protective gas and the tube diameter of the microchannel reactor are not particularly limited.

[0026] Preferably, the nickel salt, cobalt salt and manganese salt in step (1) are any one of sulfate, nitrate or chloride salts of the corresponding metal ions, or a combination of at least two of them. Typical but non-limiting combinations include a combination of sulfate and nitrate, a combination of nitrate and chloride, a combination of sulfate and chloride, or a combination of sulfate, nitrate and chloride.

[0027] Preferably, the total concentration of metal ions in the ternary salt solution in step (1) is 0.5-10 mol / L, for example, it can be 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the base solution in step (2) is a mixed solution of a precipitant solution and a complexing agent solution, and the pH value of the base solution is 9.5-11.5, for example, it can be 9.5, 9.6, 9.8, 10, 10.2, 10.4, 10.6, 10.8, 11, 11.2, 11.4 or 11.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the flow rate of the ternary salt solution in step (2) is 2-50 L / h, for example, 2 L / h, 5 L / h, 10 L / h, 15 L / h, 20 L / h, 25 L / h, 30 L / h, 35 L / h, 40 L / h, 45 L / h or 50 L / h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the precipitant solution in step (2) comprises sodium hydroxide solution and / or sodium carbonate solution.

[0031] Preferably, the concentration of the precipitant solution in step (2) is 30-40wt%, for example, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the complexing agent solution in step (2) comprises aqueous ammonia.

[0033] Preferably, the concentration of the complexing agent solution in step (2) is 10-20wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the volume ratio of the precipitant solution and the complexing agent solution in step (2) is (2-3):1, for example, it can be 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1 or 3:1, and the flow rate is based on controlling the pH value of the mixed solution between 10.2 and 10.8, for example, it can be 10.2, 10.3, 10.4, 10.5, 10.6, 10.7 or 10.8, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the protective gas in step (2) comprises nitrogen and / or argon.

[0036] Preferably, the temperature of the coprecipitation reaction in step (2) is 40-65°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the solid-liquid separation in step (2) comprises centrifugation, washing and drying performed sequentially.

[0038] Preferably, the average particle size D50 of the nickel-cobalt-manganese ternary precursor in step (2) is 5-12 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] Preferably, the lithium salt in step (3) comprises lithium carbonate.

[0040] Preferably, the solid phase sintering in step (3) is carried out in an air atmosphere.

[0041] Preferably, the temperature of the solid phase sintering in step (3) is 900-1100°C, for example, it can be 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the solid-phase sintering time in step (3) is 20-30 h, for example, it can be 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h or 30 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the metal oxide in step (4) comprises any one of aluminum oxide, zinc oxide or tin oxide, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of aluminum oxide and zinc oxide, a combination of zinc oxide and tin oxide, a combination of aluminum oxide and tin oxide, or a combination of aluminum oxide, zinc oxide and tin oxide, and aluminum oxide is further preferred.

[0044] Preferably, the phosphate in step (4) includes any one of lanthanum phosphate, aluminum phosphate or cerium phosphate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of lanthanum phosphate and aluminum phosphate, a combination of aluminum phosphate and cerium phosphate, a combination of lanthanum phosphate and cerium phosphate, or a combination of lanthanum phosphate, aluminum phosphate and cerium phosphate, and lanthanum phosphate is further preferred.

[0045] Preferably, the heat treatment in step (4) is carried out in an air atmosphere.

[0046] Preferably, the temperature of the heat treatment in step (4) is 900-1100°C, for example, it can be 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the heat treatment time in step (4) is 8-12 h, for example, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h or 12 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] As a preferred technical solution of the second aspect of the present invention, the preparation method comprises the following steps:

[0049] (1) mixing nickel salt, cobalt salt, manganese salt and deionized water to obtain a ternary salt solution with a total metal ion concentration of 0.5-10 mol / L; the nickel salt, cobalt salt and manganese salt are any one of sulfate, nitrate or chloride salts of the corresponding metal ions, or a combination of at least two of them.

[0050] (2) preparing a base liquid with a pH value of 9.5-11.5 in a microchannel reactor, and the base liquid is a mixed solution of a precipitant solution and a complexing agent solution, wherein the precipitant solution includes a sodium hydroxide solution and / or a sodium carbonate solution, and the complexing agent solution includes ammonia water; then introducing a ternary salt solution, a precipitant solution with a concentration of 30-40wt% and a complexing agent solution with a concentration of 10-20wt%, controlling the flow rate of the ternary salt solution to be 2-50L / h, and the volume ratio of the precipitant solution to the complexing agent solution to be (2-3):1, and the flow rate is based on controlling the pH value of the mixed solution to be between 10.2-10.8; at the same time, starting the material circulation, introducing nitrogen and / or argon into the microchannel reactor, so that the materials are fully mixed in the reactor, and performing a coprecipitation reaction at 40-65° C., stopping the reaction when the average particle size D50 of the precursor particles reaches 5-12 μm, and obtaining a nickel-cobalt-manganese ternary precursor after centrifugation, washing and drying.

[0051] (3) Mixing a nickel-cobalt-manganese ternary precursor and lithium carbonate, and performing solid phase sintering at 900-1100° C. for 20-30 hours in an air atmosphere to obtain a nickel-cobalt-manganese core material.

[0052] (4) The nickel-cobalt-manganese core material, aluminum oxide and lanthanum phosphate are mixed and ball-milled, and then heat-treated at 900-1100° C. for 8-12 h in an air atmosphere to obtain the co-coated ternary positive electrode material.

[0053] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the co-coated ternary positive electrode material as described in the first aspect.

[0054] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] (1) The present invention arranges a metal oxide-phosphate co-coating shell on the surface of the nickel-cobalt-manganese core. This inert material has high thermal stability. Using it as a co-coating shell significantly improves the performance of the ternary positive electrode material in a high temperature environment and reduces the risk of thermal runaway. The co-coating shell also enhances the structural stability of the ternary positive electrode material and reduces the volume expansion and contraction during the charge and discharge process, thereby extending the cycle life of the battery.

[0057] (2) The co-coated shell acts as a physical barrier, reducing the direct contact between the electrolyte and the ternary cathode material, thereby reducing the decomposition rate of the electrolyte and extending the service life of the battery. At the same time, it inhibits the dissolution of transition metals in the ternary cathode material during the charge and discharge process, reduces the concentration of metal ions in the electrolyte, thereby slowing down the attenuation of the battery capacity and improving the electrochemical performance of the material.

[0058] (3) The present invention carries out co-precipitation reaction in a microchannel reactor. Because of its internal microchannel design, it can achieve rapid and efficient material mixing, thereby ensuring the uniform distribution of reactants in the reactor, significantly improving the reaction rate and product consistency, and reducing energy consumption and costs. At the same time, the microchannel reactor can provide precise temperature control, which is crucial for the preparation process of temperature-sensitive ternary precursors. In addition, there is no dead zone in the reaction space, the materials react fully, and the obtained ternary precursor has a very high specific surface area, which further improves the electrochemical performance of the positive electrode material. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0060] Example 1

[0061] The present embodiment provides a co-coated ternary positive electrode material and a preparation method thereof, wherein the co-coated ternary positive electrode material comprises a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell; taking the total mass of the ternary positive electrode material as a calculation basis, the mass proportion of the metal oxide-phosphate co-coated shell is 12wt%.

[0062] In this embodiment, the chemical formula of the nickel-cobalt-manganese core is: Li 1.2 Ni 0.64 Co 0.08 Mn 0.08 O 2 ; In the metal oxide-phosphate co-coated shell, the metal oxide is aluminum oxide, the phosphate is lanthanum phosphate, and the mass ratio of the metal oxide to the phosphate is 1.2:1.

[0063] The preparation method provided in this embodiment comprises the following steps:

[0064] (1) Nickel sulfate, cobalt sulfate, manganese sulfate and deionized water are mixed to obtain a ternary salt solution with a total metal ion concentration of 5 mol / L.

[0065] (2) A base liquid with a pH value of 10.8 is prepared in a microchannel reactor, and the base liquid is a mixed solution of sodium hydroxide solution and ammonia water; then a ternary salt solution, a sodium hydroxide solution with a concentration of 32wt% and an ammonia water with a concentration of 18wt% are introduced, and the flow rate of the ternary salt solution is controlled to be 20L / h, the volume ratio of the sodium hydroxide solution and the ammonia water is 2.7:1, and the flow rate is controlled to control the pH value of the mixed solution between 10.2-10.8; at the same time, the material circulation is started, and nitrogen is introduced into the microchannel reactor so that the materials are fully mixed in the reactor, and a coprecipitation reaction is carried out at 52°C. The reaction is stopped when the average particle size D50 of the precursor particles reaches 8±2μm, and a nickel-cobalt-manganese ternary precursor is obtained after centrifugation, washing and drying.

[0066] (3) Mixing the nickel-cobalt-manganese ternary precursor and lithium carbonate, first heating to 50°C in an air atmosphere and keeping the temperature for 8 hours, and then continuing to heat to 1000°C for solid phase sintering for 24 hours to obtain a nickel-cobalt-manganese core material.

[0067] (4) The nickel-cobalt-manganese core material, aluminum oxide and lanthanum phosphate are mixed and ball-milled, and then heat-treated at 1000° C. for 10 h in an air atmosphere to obtain the co-coated ternary positive electrode material.

[0068] Example 2

[0069] The present embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. The co-coated ternary positive electrode material includes a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell. Taking the total mass of the ternary positive electrode material as a calculation basis, the mass proportion of the metal oxide-phosphate co-coated shell is 5wt%.

[0070] In this embodiment, the chemical formula of the nickel-cobalt-manganese core is: Li 1.5 Ni 0.6 Co 0.18 Mn 0.18 O 2 ; In the metal oxide-phosphate co-coated shell, the metal oxide is aluminum oxide, the phosphate is lanthanum phosphate, and the mass ratio of the metal oxide to the phosphate is 0.2:1.

[0071] The preparation method provided in this embodiment comprises the following steps:

[0072] (1) Nickel nitrate, cobalt nitrate, manganese nitrate and deionized water are mixed to obtain a ternary salt solution with a total metal ion concentration of 0.5 mol / L.

[0073] (2) A base liquid with a pH value of 9.5 is prepared in a microchannel reactor, and the base liquid is a mixed solution of sodium carbonate solution and ammonia water; then a ternary salt solution, a sodium carbonate solution with a concentration of 30wt% and an ammonia water with a concentration of 10wt% are introduced, and the flow rate of the ternary salt solution is controlled to be 2L / h, the volume ratio of the sodium carbonate solution and the ammonia water is 2:1, and the flow rate is controlled to control the pH value of the mixed solution between 10.2-10.8; at the same time, the material circulation is started, and argon gas is introduced into the microchannel reactor to make the materials fully mixed in the reactor, and a coprecipitation reaction is carried out at 40°C. The reaction is stopped when the average particle size D50 of the precursor particles reaches 6±1μm, and a nickel-cobalt-manganese ternary precursor is obtained after centrifugation, washing and drying.

[0074] (3) Mixing the nickel-cobalt-manganese ternary precursor and lithium carbonate, first heating to 50°C in an air atmosphere and keeping the temperature for 8 hours, and then continuing to heat to 900°C for solid phase sintering for 30 hours to obtain a nickel-cobalt-manganese core material.

[0075] (4) The nickel-cobalt-manganese core material, aluminum oxide and lanthanum phosphate are mixed and ball-milled, and then heat-treated at 900° C. for 12 h in an air atmosphere to obtain the co-coated ternary positive electrode material.

[0076] Example 3

[0077] The present embodiment provides a co-coated ternary positive electrode material and a preparation method thereof, wherein the co-coated ternary positive electrode material comprises a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell; taking the total mass of the ternary positive electrode material as a calculation basis, the mass proportion of the metal oxide-phosphate co-coated shell is 20wt%.

[0078] In this embodiment, the chemical formula of the nickel-cobalt-manganese core is: Li 1 Ni 0.8 Co 0.08 Mn 0.08 O 2 ; In the metal oxide-phosphate co-coated shell, the metal oxide is aluminum oxide, the phosphate is lanthanum phosphate, and the mass ratio of the metal oxide to the phosphate is 2:1.

[0079] The preparation method provided in this embodiment comprises the following steps:

[0080] (1) Nickel chloride, cobalt chloride, manganese chloride and deionized water are mixed to obtain a ternary salt solution with a total metal ion concentration of 10 mol / L.

[0081] (2) A base liquid with a pH value of 11.5 is prepared in a microchannel reactor, and the base liquid is a mixed solution of sodium hydroxide solution and ammonia water; then a ternary salt solution, a sodium hydroxide solution with a concentration of 40wt% and an ammonia water with a concentration of 20wt% are introduced, and the flow rate of the ternary salt solution is controlled to be 50L / h, the volume ratio of the sodium hydroxide solution and the ammonia water is 3:1, and the flow rate is controlled to control the pH value of the mixed solution between 10.2-10.8; at the same time, the material circulation is started, and nitrogen is introduced into the microchannel reactor so that the materials are fully mixed in the reactor, and a coprecipitation reaction is carried out at 65°C. The reaction is stopped when the average particle size D50 of the precursor particles reaches 10±2μm, and a nickel-cobalt-manganese ternary precursor is obtained after centrifugation, washing and drying.

[0082] (3) Mixing the nickel-cobalt-manganese ternary precursor and lithium carbonate, first heating to 50°C in an air atmosphere and keeping the temperature for 8 hours, and then continuing to heat to 1100°C for solid phase sintering for 20 hours to obtain a nickel-cobalt-manganese core material.

[0083] (4) The nickel-cobalt-manganese core material, aluminum oxide and lanthanum phosphate are mixed and ball-milled, and then heat-treated at 1100° C. for 8 h in an air atmosphere to obtain the co-coated ternary positive electrode material.

[0084] Example 4

[0085] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except for replacing aluminum oxide with an equal mass of zinc oxide and replacing lanthanum phosphate with an equal mass of aluminum phosphate, the remaining steps and conditions are the same as those in Example 1 and are therefore not described in detail here.

[0086] Example 5

[0087] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except that aluminum oxide is replaced by an equal mass of tin oxide, and lanthanum phosphate is replaced by an equal mass of cerium phosphate, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.

[0088] Example 6

[0089] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except for changing the mass ratio of metal oxide to phosphate to 0.1:1, the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0090] Example 7

[0091] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except for changing the mass ratio of metal oxide to phosphate to 2.5:1, the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0092] Example 8

[0093] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except that the temperature of the coprecipitation reaction is changed to 35° C., the remaining steps and conditions are the same as those in Example 1, so they are not described here in detail.

[0094] Example 9

[0095] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except that the temperature of the coprecipitation reaction is changed to 70° C., the remaining steps and conditions are the same as those in Example 1, so they are not described here in detail.

[0096] Example 10

[0097] This embodiment provides a co-coated ternary positive electrode material and a preparation method thereof. Except that the temperature of the heat treatment in step (4) is changed to 800° C., the remaining steps and conditions are the same as those in Example 1 and are not described in detail here.

[0098] Comparative Example 1

[0099] This comparative example provides a ternary positive electrode material and a preparation method thereof, except that no aluminum oxide is added in step (4), that is, only the nickel-cobalt-manganese core is coated with lanthanum phosphate, and the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0100] Comparative Example 2

[0101] This comparative example provides a ternary positive electrode material and a preparation method thereof, except that lanthanum phosphate is not added in step (4), that is, only the nickel-cobalt-manganese core is coated with aluminum oxide. The remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0102] Comparative Example 3

[0103] This comparative example provides a ternary positive electrode material and a preparation method thereof. Except for deleting step (4), that is, directly using the nickel-cobalt-manganese core material as the ternary positive electrode material, the remaining steps and conditions are the same as those in Example 1, so they are not repeated here.

[0104] Comparative Example 4

[0105] This comparative example provides a co-coated ternary positive electrode material and a preparation method thereof. Except that the microchannel reactor used in step (2) is replaced by a conventional reactor, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.

[0106] It should be noted that compared with Example 1, since the microchannel reactor in this comparative example is replaced by a conventional reactor, the reaction efficiency is significantly reduced. The time required for the average particle size D50 of the precursor particles to reach 8±2μm is about three times that of Example 1, and during the reaction process, the temperature control accuracy of the conventional reactor is significantly lower than that of the microchannel reactor.

[0107] Performance Test:

[0108] The ternary positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-4 were used to prepare button-type lithium-ion batteries. The specific preparation method includes: dropping the positive electrode material, acetylene black and polyvinylidene fluoride into N-methyl-2-pyridine alkanone in a mass ratio of 8:1:1 to prepare a solution, and then evenly applying it on an aluminum foil, drying and stamping it into a thin sheet; the battery pole piece, the single lithium sheet, the glass fiber separator, the electrolyte (LiClO 4 ) The gasket, shrapnel and battery shell are assembled into a button battery in an argon glove box.

[0109] Table 1 below shows the electrochemical performance test data of button-type batteries prepared using the ternary positive electrode materials obtained in Examples 1-10 and Comparative Examples 1-4, respectively.

[0110] Table 1

[0111]

[0112] It can be seen that the present invention arranges a metal oxide-phosphate co-coating shell on the surface of the nickel-cobalt-manganese core. This inert material has high thermal stability. Using it as a co-coating shell significantly improves the performance of the ternary positive electrode material in a high temperature environment and reduces the risk of thermal runaway. The co-coating shell enhances the structural stability of the ternary positive electrode material and reduces the volume expansion and contraction during the charge and discharge process, thereby extending the cycle life of the battery.

[0113] In addition, the co-coated shell acts as a physical barrier, reducing the direct contact between the electrolyte and the ternary positive electrode material, thereby reducing the decomposition rate of the electrolyte and extending the service life of the battery. At the same time, it inhibits the dissolution of transition metals in the ternary positive electrode material during the charge and discharge process, reduces the concentration of metal ions in the electrolyte, thereby slowing down the attenuation of the battery capacity and improving the electrochemical performance of the material.

[0114] Furthermore, the present invention carries out a co-precipitation reaction in a microchannel reactor, because its internal microchannel design can achieve fast and efficient material mixing, thereby ensuring the uniform distribution of the reactants in the reactor, significantly improving the reaction rate and product consistency, and reducing energy consumption and costs. At the same time, the microchannel reactor can provide precise temperature control, which is crucial for the preparation process of temperature-sensitive ternary precursors. There is no dead zone in the reaction space, the materials react fully, and the obtained ternary precursor has a very high specific surface area, which further improves the electrochemical properties of the positive electrode material.

[0115] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A co-coated ternary positive electrode material, characterized in that: The co-coated ternary positive electrode material comprises a nickel-cobalt-manganese core and a metal oxide-phosphate co-coated shell; Taking the total mass of the ternary positive electrode material as a calculation basis, the mass proportion of the metal oxide-phosphate co-coated shell is 5-20wt%.

2. The co-coated ternary positive electrode material according to claim 1, characterized in that: The chemical formula of the nickel-cobalt-manganese core is: Li a Ni x Co y Mn z O2; wherein, 1≤a≤1.5, 0.6≤x≤0.8, 0.08≤y≤0.18, and x+y+z≤1.

3. The co-coated ternary positive electrode material according to claim 1 or 2, characterized in that: In the metal oxide-phosphate co-coated shell, the metal oxide includes any one of aluminum oxide, zinc oxide or tin oxide or a combination of at least two thereof, and aluminum oxide is more preferred; Preferably, in the metal oxide-phosphate co-coated shell, the phosphate includes any one or a combination of at least two of lanthanum phosphate, aluminum phosphate or cerium phosphate, and is further preferably lanthanum phosphate; Preferably, in the metal oxide-phosphate co-coated shell, the mass ratio of metal oxide to phosphate is (0.2-2):

1.

4. A method for preparing a co-coated ternary positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing nickel salt, cobalt salt, manganese salt and deionized water to obtain a ternary salt solution; (2) preparing a base liquid in a microchannel reactor, then introducing a ternary salt solution, a precipitant solution and a complexing agent solution, and simultaneously starting material circulation, introducing a protective gas into the microchannel reactor, so that the materials are fully mixed in the reactor for a coprecipitation reaction, and obtaining a nickel-cobalt-manganese ternary precursor after solid-liquid separation; (3) mixing a nickel-cobalt-manganese ternary precursor and a lithium salt for solid phase sintering to obtain a nickel-cobalt-manganese core material; (4) Mixing the nickel-cobalt-manganese core material, metal oxide and phosphate, and subjecting them to ball milling and heat treatment in sequence to obtain the co-coated ternary positive electrode material.

5. The preparation method according to claim 4, characterized in that: The nickel salt, cobalt salt and manganese salt in step (1) are any one of sulfate, nitrate or chloride salts of the corresponding metal ions, or a combination of at least two thereof; Preferably, the total concentration of metal ions in the ternary salt solution in step (1) is 0.5-10 mol / L.

6. The preparation method according to claim 4 or 5, characterized in that: The base solution in step (2) is a mixed solution of a precipitant solution and a complexing agent solution, and the pH value of the base solution is 9.5-11.5; Preferably, the flow rate of the ternary salt solution in step (2) is 2-50 L / h; Preferably, the precipitant solution in step (2) comprises sodium hydroxide solution and / or sodium carbonate solution; Preferably, the concentration of the precipitant solution in step (2) is 30-40 wt %; Preferably, the complexing agent solution in step (2) comprises aqueous ammonia; Preferably, the concentration of the complexing agent solution in step (2) is 10-20wt%; Preferably, the volume ratio of the precipitant solution and the complexing agent solution in step (2) is (2-3):1, and the flow rate is controlled to control the pH value of the mixed solution between 10.2-10.8; Preferably, the protective gas in step (2) comprises nitrogen and / or argon; Preferably, the temperature of the coprecipitation reaction in step (2) is 40-65°C; Preferably, the solid-liquid separation in step (2) comprises centrifugation, washing and drying performed sequentially; Preferably, the average particle size D50 of the nickel-cobalt-manganese ternary precursor in step (2) is 5-12 μm.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The lithium salt in step (3) includes lithium carbonate; Preferably, the solid phase sintering in step (3) is carried out in an air atmosphere; Preferably, the temperature of the solid phase sintering in step (3) is 900-1100° C. Preferably, the solid phase sintering time in step (3) is 20-30 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The metal oxide in step (4) comprises any one of aluminum oxide, zinc oxide or tin oxide, or a combination of at least two thereof, and aluminum oxide is more preferably used; Preferably, the phosphate in step (4) comprises any one or a combination of at least two of lanthanum phosphate, aluminum phosphate or cerium phosphate, and more preferably lanthanum phosphate; Preferably, the heat treatment in step (4) is carried out in an air atmosphere; Preferably, the temperature of the heat treatment in step (4) is 900-1100°C; Preferably, the heat treatment time in step (4) is 8-12 hours.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method comprises the following steps: (1) mixing a nickel salt, a cobalt salt, a manganese salt and deionized water to obtain a ternary salt solution with a total metal ion concentration of 0.5-10 mol / L; wherein the nickel salt, the cobalt salt and the manganese salt are any one of sulfate, nitrate or chloride salts of the corresponding metal ions, or a combination of at least two of them; (2) preparing a base liquid with a pH value of 9.5-11.5 in a microchannel reactor, and the base liquid is a mixed solution of a precipitant solution and a complexing agent solution, wherein the precipitant solution includes a sodium hydroxide solution and / or a sodium carbonate solution, and the complexing agent solution includes ammonia water; then introducing a ternary salt solution, a precipitant solution with a concentration of 30-40wt% and a complexing agent solution with a concentration of 10-20wt%, controlling the flow rate of the ternary salt solution to be 2-50L / h, the volume ratio of the precipitant solution to the complexing agent solution to be (2-3):1, and the flow rate is based on controlling the pH value of the mixed solution to be between 10.2-10.8; at the same time, starting the material circulation, introducing nitrogen and / or argon into the microchannel reactor, so that the materials are fully mixed in the reactor, and performing a coprecipitation reaction at 40-65° C., stopping the reaction when the average particle size D50 of the precursor particles reaches 5-12 μm, and obtaining a nickel-cobalt-manganese ternary precursor after centrifugation, washing and drying; (3) mixing a nickel-cobalt-manganese ternary precursor and lithium carbonate, and performing solid phase sintering at 900-1100° C. for 20-30 hours in an air atmosphere to obtain a nickel-cobalt-manganese core material; (4) The nickel-cobalt-manganese core material, aluminum oxide and lanthanum phosphate are mixed and ball-milled, and then heat-treated at 900-1100° C. for 8-12 h in an air atmosphere to obtain the co-coated ternary positive electrode material.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the co-coated ternary positive electrode material as described in any one of claims 1 to 3.